HOT WELD METAL GRINDING WITH SOFT AND MEDIUM-SOFT WHEELS - Nikolay I. Boyko; Konstantin S. Fisenko (Advanced Engineering Research, 2012)
The hot weld metal grinding of the cylindrical parts with soft and medium-soft wheels is investigated. Work-time wheel wear charts and grinding cutting force diagrams received through the test and calculation data are offered. Applicable equations for the cutting forces occurring in the wheel — workpiece interaction, depending on the grinding conditions through the hot weld metal grinding of the barrels with the soft and medium-soft wheels at the welding arc burn-out and cutter withdrawal moment, are developed.